KARAKTERISTIK KIMIAWI DARI DAGING KERANG TAHU, KERANG SALJU DAN KEONG MACAN - Asadatun Abdullah; Nurjanah Nurjanah; Taufik Hidayat; Rizky Chairunisah (Jurnal Teknologi dan Industri Pangan, 2017)
Meretrix meretrix, Pholas dactylus and Babylonia spirata are potential fisheries commodity, but information about their nutritional values is still limited. This research was aimed to determine the chemical compositions of Meretrix meretrix, Pholas dactylus and Babylonia spirata. Proximate of Meretrix meretrix, Pholas dactylus and Babylonia spirata were analyzed using thermogravimetric, soxhlet and kjeldahl methods. Their amino acid composition and taurine content were analyzed using High Performance Liquid Chromatografy (HPLC). The moisture, ash, fat, protein and carbohydrate contents of Meretrix meretrix were 79.98%, 1.37 0.11 9.39 and 9.02 respectively; Pholas dactylus were 83.78%, 1.19, 0.11, 11.37 and 3.55 respectively; while Babylonia spirata 78.44, 1.20, 0.33, 17.38 and 2.65 respectively. Arginine was the highest essential amino acid found in Meretrix meretrix, Pholas dactylus and Babylonia spirata meat with values of 1.12%, 0.93 dan 2.50 respectively. Glutamic acid was the most abundant non-essential amino acid with the highest value of 2.24, 2.14 and 3.76. The limiting amino acid was histidine with the value of 0.25%, 0.18 and 0.34, respectively. The taurine content of Pholas dactylus meat (0.085%) was higher than the Babylonia spirata and Meretrix meretrix (0.067 and 0.062%, respectively).